Indole-3-Butyric Acid (IBA) as Key Drivers of Rooting Success in Dragon Fruit (Hylocereus Spp.) Stem Cuttings – A Review - Singh, Ajaypartap; Chander, Subhash; Kumari, Loveleen; Kumar, Shiv (International Journal of Economic Plants, 2025)
Dragon fruit (Hylocereus spp.), a climbing cactus with significant nutritional and economic value, is primarily propagated through stem cuttings due to its efficiency and genetic uniformity. This review focuses on optimizing propagation practices, particularly the role of auxin application specifically indole-3-butyric acid (IBA) in enhancing rooting and shoot development. IBA, an exogenously applied plant growth regulator, is widely preferred over other auxins due to its superior rooting efficiency, lower toxicity, and ability to promote both primary and lateral root development. It plays a vital role in adventitious root and shoot initiation by stimulating cell division, elongation, and differentiation. This review synthesized recent findings on the mechanisms by which IBA, a key regulator of hormonal, biochemical, and physiological processes enhances propagation efficiency in dragon fruit and offers practical recommendations for sustainable propagation to ensure high-quality plant material for commercial cultivation. This review further explores the effects of different IBA concentrations on root parameters, shoot growth, and overall cutting success in dragon fruit. Additionally, the physiological and biochemical responses of stem cuttings to IBA application such as enhanced carbohydrate mobilization, enzyme activation, and phenolic compound dynamics are discussed to provide a comprehensive understanding of its mode of action. By offering practical recommendations for IBA use, this review supports the development of efficient and sustainable propagation strategies to ensure consistent, high-quality planting material for commercial cultivation in tropical and subtropical regions.